Impact of Price, Risk and Shipping Insurance Claims on E-Commerce Gadgets Purchase Decisions - Rizka Afriani; Nurul Jannah; Budi Harianto (Dinasti International Journal of Economics, Finance & Accounting, 2024)
When shopping for gadgets online, a person often feels worried if their shopping activity ends in fraud. Lack of confidence in online shopping is experienced by some consumers which makes them no longer want to buy gadgets on online shopping sites. The risk of buying a gadget in online shopping is huge. Starting from the risk of goods being damaged during shipment, theft, goods not arriving and much more. The aim of this study is to demonstrate the influence of the price, risk and claims of shipping insurance on the decision to buy gadgets in E-commerce. This research uses quantitative methods with double linear regression analysis. Research results show that prices influence purchasing decisions, risks influence purchase decisions, and insurance claims influence buying decisions.